PEMBELAJARAN MENGGUNAKAN SASTRA TRADISIONAL UNTUK MENINGKATKAN KEMAMPUAN SOSIAL-EMOSIONAL ANAK KELOMPOK A DI TK MELATI - Irwan, Irwan; Abdullah, Rudi (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2023)
This study aims to: determine the application of learning using traditional literature in Melati Kindergarten; the social-emotional abilities of group B children using traditional literature learning in Melati Kindergarten;The type of research used in this research is qualitative research. The analysis model used is an interactive model. In collecting data, using observation, interviews, and documentation. Data validity tests in this study include credibility and dependability tests. The results of the study stated that traditional literature learning was implemented in the Melati Kindergarten using legends, animal stories, and fairy tales carried out in the initial activities. Legend stories, animal stories, and fairy tales read by teachers can give pleasure to children, develop imagination, the characters in stories can teach children how to behave in social life, and these stories contain values that can develop aspects of child development. At the end of the learning activities an assessment of children's abilities is carried out, the application of traditional literature with the learning steps that have been carried out can bring out and improve children's social-emotional abilities.